Humanization and Integrality in Family Care: the perception of mothers about pregnancy of their teenage daughters - Almeida de Araújo, Jeane; Halboth, Nadia Veronica; Araújo, Alisson (O Mundo da Saúde, 2012)
In view of the need of humanization in primary care to change it into integral care, the goal of this study was to understand the perception of mothers about having a pregnant teenage daughter. A study conducted with 10 mothers of pregnant adolescents living in areas covered three units of the Family Health Strategy in Diamantina-MG. This is a qualitative research in which data were collected by means of individual open interviews. The interviews were recorded, transcribed verbatim, and then the material was subjected to discourse analysis. We observed varied feelings of mothers before having pregnant daughters: joy, disappointment, conformity and fear, both related to the burden of their daughters caring for a child, and consequences such as the interruption of studies. Results showed the need for health professionals to care for mothers of pregnant adolescents because their perceptions about the pregnancy of their daughters are crucial to family adaptation and support, and also to induce an attitude of responsibility and care on the part of teenagers. The findings also revealed recurrence of teenage pregnancy and the repetition by teenagers of their mothers’ history, which indicates a strong component of the vicious cycle of teenagers’ pregnancy in poor communities, in part due to the difficulties of guidance from family, school and health services. Humane care and help by family health teams, guided by the humanization attitude, is highlighted as essential to improving the care of the binomy mother-pregnant teenager daughter.